Pharmacological CLK inhibition disrupts SR protein function and RNA splicing blocking cell growth and migration in TNBC - Nasi Liu; Jurjun J. S. van der Velde; Sherien Ramdjielal; Esmee Koedoot; Nila K. van Overbeek; Daisy Batenburg; Alfred C. O. Vertegaal; Bob van de Water; Sylvia E. Le Dévédec (Breast Cancer Research)
Abstract Background Dysregulation of alternative splicing plays a pivotal role in tumorigenesis and metastasis in triple-negative breast cancer (TNBC). Serine/arginine-rich (SR) proteins, essential components of the spliceosome, undergo phosphorylation by Cdc2-like kinase (CLK). Here we explored the impact of pharmacological inhibition of CLK using a novel inhibitor, T-025, on the spliceosome complex and transcriptional responses in relation to cell proliferation and migration in TNBC. Methods We evaluated the anti-proliferative and anti-migratory efficacy of T-025 in a spectrum of TNBC cell lines. Fluorescent reporter cell lines and flowcytometry were used to determine the effect of T-025 on cell cycle. Deep RNA sequencing was performed to unravel the differentially expressed genes (DEGs) and alternatively spliced genes (ASGs) upon T-025 treatment. Pulldown/MS was used to uncover the impact of T-025 on SRSF7 interactome. Live-cell imaging and photobleaching experiments were conducted to determine the subnuclear localization of SRSF7-GFP and its dynamic mobility. Results T-025 exhibited a potent anti-proliferative effect in a spectrum of TNBC cell lines, particularly in highly proliferative cell lines. Treatment with T-025 induced cell cycle arrest in the G1-S phase, resulting in an increased proportion of aneuploidy cells and cells with 4 N DNA. T-025 significantly inhibited cell migration in highly migratory TNBC cell lines. Deep RNA sequencing uncovered numerous DEGs and ASGs upon T-025 treatment, which were significantly enriched in pathways related to cell division, RNA splicing and cell migration. Pulldown/MS showed that SRSF7 interacted more with nuclear-speckle-residing proteins, while less with RNA helicases and polymerases upon T-025 treatment. Enhanced interactions between SRSF7 and other phosphorylated SR proteins localized at nuclear speckles were also observed. Live-cell imaging indicated that T-025 treatment induced the accumulation of SRSF7-GFP at nuclear speckles and nuclear speckles’ enlargement, restricting its protein dynamic mobility. Conclusions CLK inhibition using T-025 leads to the accumulation of splicing factors at nuclear speckles and stalls their release to splicing sites, resulting in the RNA splicing reprogramming of a large number of genes involved in cell division, migration and RNA splicing. Our findings provide evidence that T-025 could be a promising therapeutic drug for TNBC patients.